Zakat dalam Pendidikan Islam Perspektif Maqâshid Al-Sharî’ah - Muhamad Sofi Mubarok (Al-Mau'izhoh, 2023)
This study aims to reveal the values and principles of maqâshid al-syarî'ah in zakat fiqh which is one of the studies in Islamic education that aims to meet the needs while simultaneously driving the mustadh'afin economy, with a focus on zakat verses and the views of contemporary scholars on zakat fiqh , as well as reveal the values of Islamic Education in zakat. The method used in this research is content analysis involving a systematic process to identify, classify, and interpret various Al-Qur'anic texts related to zakat. This research also involves historical analysis to see the context of the obligation of zakat as the previous Shari'a in an effort to break down poverty. The results of the study show that although viewed from the aspect of 'ubûdiyyah zakat is a religious doctrine that is rigid, rigid and axiomatic in nature (ma'lûmun minad-dîn bid-dharûrah), the legal doctrine of muamalah and the disclosure of the values of Islamic Education open up the possibility of ijtihad new to fiqh zakat. Maqashid al-shari'ah introduces a new alternative and perspective on zakat as an integral part of the conception of prayer, so that the hierarchy of pillars of Islam that places zakat in third place is necessary because the obligation to pray always goes hand in hand with the obligation to pay zakat. At the same time, there is a need to re-discuss the terminology of scholars regarding al-tsawâbit and al-mutaghayyirât, so that some of the views of contemporary scholars who try to expand the fiqh of zakat should be considered.